Estimation of the anaerobic threshold from heart rate variability in an incremental swimming test - Di Michele, R.; Gatta, G.; Di Leo, A.; Cortesi, M.; Andina, F.; Tam, E.; da Boit, M.; Merni, F. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to evaluate, in swimming, the agreement between the anaerobic threshold (AT) as determined from the analysis of blood lactate concentration ([La]) and from a new method based on the heart rate (HR) variability (HRV). Fourteen high-level swimmers completed an incremental 7 × 200-m front crawl test, during which the HRV was measured continuously and [La] was collected after each step. To individuate the AT, the trends of the high-frequency HRV spectral power (HFPOW) and of the fraction of HFPOW relative to the respiratory sinus arrhythmia (HFPOW-RSA) were analyzed. In all the subjects, an abrupt increase of both HFPOW and HFPOW-RSA was observed and associated with the AT. The AT parameters determined, respectively, from [La] and HFPOW-RSA were similar (p > 0.05) and highly correlated (HR: 182.0 ± 8.1 vs. 181.1 ± 8.2 b/min, r = 0.93, 95% limits of agreement [LoA]: -6.7 to 4.9 b/min; velocity: 1.47 ± 0.11 vs. 1.47 ± 0.11 m/s, r = 0.98, 95% LoA: -0.05 to 0.05 m/s). Instead, the AT HR and velocity obtained from HFPOW (179.2 ± 8.4 b/min; 1.45 ± 0.11 m/s) were correlated to the corresponding parameters determined from [La] (HR: r = 0.84; velocity: r = 0.94) but underestimated them slightly (95% LoA: -11.9 to 6.3 b/min and -0.11 to 0.05 m/s). These results demonstrate that the AT can be assessed from the HRV in swimming, providing an important testing tool for coaches. Furthermore, using the actual respiratory spectral component, rather than the total HF spectral power, allows us to obtain a more accurate estimate of AT parameters.